Does Toxoplasma gondii Infection Affect the Levels of IgE and Cytokines (IL-5, IL-6, IL-10, IL-12, and TNF-alpha)? - Matowicka Karna, Joanna; Kemona, Halina; Dymicka-Piekarska, Violetta (Clinical & developmental immunology, 2009)
In the study performed in a group of patients infected withT. gondii, we evaluated Th2 humoral response(IL-5, IL-6, IL-10) and Th1 cell response (IL-12, TNF-α). The study objective was to assess the effect ofT. gondii on chosen indices of the immuneresponse. The study involved 52 women infected withT. gondii (aged 18–42 years) prior toantiparasitic treatment. In all the patients, we found IgM (index>0.7) and IgG which exceeded 300 IU/ml. The controlgroup (C) consisted of 40 healthy women aged 18–46 years. Inthe study group (T) and in the control group (C), the levels ofIgE, IL-5, IL-6, IL-10, IL-12, and TNF-α were determined. In our study,T. gondii patients had twofold higher levels ofIL-5 and IL-6 as compared to healthy subjects, which seems toconfirm the presence of an inflammatory state. We found the levelof IL-10 to be fivefold higher in the course oftoxoplasmosis than in healthy controls. Thelevels of IL-12 and TNF-α were comparable to those observed in healthy controls.The study has revealed that that patients infected withT. gondii show increased production of the humoralresponse cytokines, whereas the generation of the cell responsecytokines remains unchanged.